Gender, Lingkungan Keluarga, Pengalaman Kerja dan Minat Mahasiswa Mengikuti Pendidikan Profesi Akuntansi (PPAk) - Diah Paramitha, I Gusti Ayu; Sukartha, P. D'Yan Yaniartha (E-Jurnal Akuntansi; Vol 33 No 2 (2023), 2023)
Accounting Profession Education (PPAk) is the choice of further education level for bachelor of economics majoring in accounting for a career as a professional accountant. The aim of this research is to empirically examine the effect of gender, family environment, and work experience on students' interest in participating in PPAk. This research uses a quantitative approach. The sample was determined by nonprobability sampling method using saturated sampling technique. The number of samples used in this study were 46 respondents, namely Accounting Professional Education students. This research uses multiple linear regression analysis techniques. The results showed that family environment and work experience had a positive effect on students' interest in taking PPAk, while gender had no effect on students' interest in taking PPAk. Keywords: Gender, Family Environment, Work experience, Accounting Profession Education.